Cultural Resilience and Identity Narratives: The Role of Patna's Historical Monuments in Shaping Regional Collective Memory (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper explores the evolving role of historical monuments in Patna as active agents of cultural resilience and identity formation in post-colonial India. The purpose of this research is to analyse how monuments such as Golghar, Patna Sahib, Mahavir Mandir, and Patna Museum have been reinterpreted throughout the course of time through public memory, religious practice, political narratives, and institutional frameworks. Rather than considering these sites as static remnants of the past, the analysis focusses on how these monuments have been reinterpreted. The study illustrates the manner in which these cultural structures have resisted colonial upheavals and been absorbed into present regional identity. It does so by drawing from a historical synthesis of sources that have been documented. By performing a variety of functions, ranging from curatorial narrative and symbolic resistance to spiritual anchoring and community remembering, each monument contributes to the maintenance of cultural continuity throughout generations.A further focus of the article is an examination of the interconnections between political symbolism and public involvement with heritage. Particular attention is paid to the manner in which these locations have been hijacked by both state-led urban development schemes and grassroots cultural efforts. These places have been turned into venues for conversation, negotiation, and the reaffirmation of regional pride, according to the findings of this study, which reveals that the nature of communal memory in Patna is always altering. This study highlights the importance of implementing heritage policies that are more inclusive and that take into account local narratives. Additionally, it suggests incorporating cultural heritage into educational systems and governance frameworks in order to guarantee the preservation of cultural heritage in a sustainable manner and to promote meaningful public engagement.Consequently, the article frames Patna's monuments as living manifestations of the city's cultural memory, which is closely linked with the city's socio-political history that has occurred throughout time. Their research not only makes a contribution to the general knowledge of the dynamics of regional identity, but it also provides insights into the more general processes of cultural affirmation that occur in post-colonial nations.